Problem-Based Learning with Multilevel Representation: A Strategy to Master the Ionic Equilibrium in Solution Concepts - Hamid, Abdul; Hikmah, Nur; Sholahuddin, Arif (JTK (Jurnal Tadris Kimiya), 2022)
Mastery of abstract chemistry concepts requires learning strategies to facilitate students to make mental imagery to the submicroscopic level. This study aims to analyze the differences in students’ mastery of the ionic equilibrium in salt solutions concept by applying the Problem-Based Learning (PBL) model with multilevel representation. The study applied a quasi-experimental method with a pretest-posttest non-equivalent control group design. The research samples were 61 students of natural science 11th grade SMAN 6 Banjarmasin, which were determined by random cluster sampling. This test instrument is in the form of reasoned-multiple choice with a Content Validity Ratio (CVR) score of 1 (valid), reliability score of 0.96 (very high), difficulty index is moderate to difficult, distinguishing power is moderate to good, and sensitivity item is a sensitive category. Data were analyzed inferentially using an unpaired ttest. This research found that the PBL model with multilevel representation increased the studentsâ€™ thinking ability at Higher Order Thinking Skills (HOTS) levels. The student’s mastery of the ionic equilibrium in salt solutions concept learned by using the PBL model with multilevel representation was better than by using the PBL model.